Enhancing Productivity of Ailanthus excelsa Roxb. by Planting Grafted Female Trees - Tomar, U. K.; Rathore, T. R.; Bala, N. (Indian Forester, 2019)
Ailanthus excelsa (Ardu), a dioecious tree species, is an important fodder tree of Rajasthan. It is also valued for timber, fuel-wood and ethno-medicines in many parts of India. Literature and field observations indicate that female plants of this specie exhibit better growth forms as compared to male plants. However, it is hard to identify female plants at the sapling stage. Cloning of Ardu through macro and micro-propagation methods is difficult and economically non-viable. Using grafting method developed and improved by Arid Forest Research Institute (AFRI) a trial of male and female plants was established in August 2008. The result shows that female trees are superior to male trees in all the parameters except the length of primary root. Maximum difference was observed in the leave fresh (fodder) weight and number of branches, in which 71% and 69% higher biomass was recorded in female plants, respectively. Economics of this trial revealed that the higher cost of raising grafted female plantations is recovered within five years through fodder component only. Twenty per cent higher wood (timber and fuel) production by female plants is a benefit over plants raised through seedling with an assumption that plantations raised through seedlings have 50% male plants.